2017
DOI: 10.1038/cddis.2016.468
|View full text |Cite
|
Sign up to set email alerts
|

The TAZ–miR-224–SMAD4 axis promotes tumorigenesis in osteosarcoma

Abstract: Transcriptional co-activator with PDZ-binding motif (TAZ) is a downstream effector of the Hippo signaling pathway that participates in tumorigenesis. The aim of this study was to identify the miRNA counterpart for TAZ and elucidate the mechanism underlying the tumorigenic effect of TAZ. We demonstrated that TAZ is upregulated in osteosarcoma (OS) tissues and cell lines, and that TAZ overexpression can induce cell migration, invasion and proliferation. Moreover, miRNA-224 (miR-224), a TAZ phenocopy that functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 43 publications
3
23
2
Order By: Relevance
“…It is therefore not surprising that YAP/TAZ play an important role in osteogenesis. Moreover, incorporation of α-smooth muscle actin in contractile stress fibers of MSC favor osteogenic differentiation in a YAP-dependent fashion [150]. In fact, YAP depletion was shown to downregulate the expression of osteogenic genes and of focal adhesion components paxillin, β-1 integrin and zyxin in human MSC in vitro [151].…”
Section: Yap and Taz As Regulators Of Osteogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…It is therefore not surprising that YAP/TAZ play an important role in osteogenesis. Moreover, incorporation of α-smooth muscle actin in contractile stress fibers of MSC favor osteogenic differentiation in a YAP-dependent fashion [150]. In fact, YAP depletion was shown to downregulate the expression of osteogenic genes and of focal adhesion components paxillin, β-1 integrin and zyxin in human MSC in vitro [151].…”
Section: Yap and Taz As Regulators Of Osteogenesismentioning
confidence: 99%
“…Hsa-miR-135b overexpression was demonstrated to increase osteosarcoma xenograft growth [196]. Likewise, hsa-miR-224 was described as a TAZ/TEAD directly-activated target gene that enhances the proliferation and tumorigenicity of osteosarcoma and was demonstrated to rescue the migration, invasion and tumorigenicity of osteosarcoma cells upon TAZ knockdown at least in part through targeting SMAD4 [150]. Thus, it is possible that YAP and TAZ serve distinct functions in osteosarcoma pathogenesis and progression.…”
Section: Yap/taz In Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from downstream target proteins, several recent studies have revealed that YAP and TAZ also regulate the expression of microRNAs [ 89 , 282 , 362 , 363 , 364 , 365 , 366 , 367 ]. Bertero and colleagues found that YAP/TAZ activation promoted the expression of the miR-130/301 family, which in turn enhanced collagen deposition and ECM remodeling to further enhance YAP activity [ 365 ].…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%
“…YAP and TAZ regulate miR-25, miR-93, and miR-106b to promote non-small cell lung cancer proliferation [ 363 ], and these miRNAs are overexpressed in lung, breast, and head and neck cancers [ 363 ]. TAZ can regulate miR135b and miR224 to promote EMT and tumorigenesis in osteosarcoma [ 366 , 367 ]. Evidence also shows that YAP can repress miRNA processing in cancer cells [ 368 ], and that YAP and TAZ can also regulate pre-miRNA processing through Dicer [ 369 ].…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%